Ca2+ dynamics between mitochondria and the endoplasmic reticulum - Graier, Wolfgang (Henry Stewart Talks, 2007)
3D structure of the endoplasmic reticulum and mitochondria, Techniques to measure organelle calcium, Mitochondrial functions, Principles of mitochondrial calcium signaling, Functional coupling of the endoplasmic reticulum and the mitochondria, Consequences of alterations in the structural integrity of the mitochondria, Subplasmalemmal mitochondrial calcium buffering, Physiological importance of mitochondrial calcium uptake, The cellular calcium cycle